Pengaruh Negara Asal terhadap Kualitas yang Dirasakan dengan Etnosentris Konsumen sebagai Variable Moderasi Perspektif Bisnis Islam - Muhammad Daffa Hariyanto; Fatih Fuadi; Suhendar; Habibi, Ahmad (Al-Ulum, 2024)
The purpose of this study was to determine whether the Country of Origin effect on Perceived Quality with ethnocentric consumers as a variable of moderation. This study aims to find out what the influence of the country of Origin on perceived quality with consumer ethnocentrism as a variable of moderation. This study uses a quantitative approach. The population used is Uniqlo brand consumers in Bandar Lampung City with an unknown population. The number of samples was calculated using the Lemeshow formula and the result obtained was 100 samples. The application used in analyzing data is SmartPLS with structural equation model (SEM) approach. The results showed that Country of Origin can have a positive and significant influence on Perceived Quality. And Consumer ethnocentricity cannot moderate the influence of Country of Origin on Perceived Quality.